Analysis of the Health Level of Sharia Banks Using the RGEC Method in 2019-2023 - Said, Wan Aziza Said; Huda, Miftahul; Muna, Izzatul; Emiarti, Endah (Journal of Islamic Economics and Philanthropy, 2025)
Indonesia embraces a dual banking framework where both conventional and Sharia banks operate simultaneously. This coexistence allows a diverse range of financial services to cater to various customer needs. Despite this, Sharia banking accounts for only 7.3% of the nation’s total banking sector. This limited market share is indicative of challenges such as lower public awareness and less competitive financial products compared to conventional banks. Therefore, assessing the health of Sharia banks is essential for ensuring their sustainability, enhancing financial stability, and building public trust in their operations.This research examines the health of Sharia banks from 2019 to 2023, using the RGEC (Risk Profile, Good Corporate Governance, Earning, and Capital) method. A quantitative approach with descriptive analysis reveals that, on average, Sharia banks demonstrated varying degrees of health, with some excelling while others struggled to meet standards set by regulatory bodies. The result of this study is that in 2019 the health of Sharia commercial banks was ranked "quite healthy" which then improved in 2020 by getting a "healthy" rating, in the last 3 years the health of Sharia commercial banks has declined again with a rating of "quite healthy". The findings of this researc highlight specific areas for improvement and strategic growth within the sector.